Efeitos agudos da administração de pressão positiva contínua em vias aéreas de modo não invasivo sobre o parênquima pulmonar de voluntários sadios nas posições supina e prona: alterações na tomografia computadorizada de alta resolução - Winkeler, Geórgia Freire Paiva (2006)
Introduction: Noninvasive positive-pressure ventilation (NIPPV) is an effective means of treating patients with acute respiratory failure and its use has been well established in cardiogenic pulmonary edema and in exacerbations of chronic obstructive pulmonary disease (COPD), reducing the need for endotracheal intubation and improving survival. Furthermore the continuous positive airway pressure (CPAP) – a mode of NIPPV – is the recommended treatment for obstructive sleep apnea syndrome (OSAS), where frequently there is no abnormality in pulmonary parenchyma. Also in the acute respiratory distress syndrome (ARDS), the application of positive end-expiratory pressure (PEEP) may result in alveolar recruitment of nonaerated units as well as in overinflation of the aerated lung areas. Alveolar overinflation is considered an important factor related to ventilator-induced lung injury causing higher mortality. The prone position has beneficial effects on oxygenation in these patients and the additive effect of PEEP with this maneuver is debatable. High resolution computed tomography (HRCT) is an excellent imaging method to evaluate the effects of positive pressure and prone position on pulmonary parenchyma. Objectives: To evaluate the effects of CPAP applied by a nasal mask on pulmonary inflation in normal subjects in supine and prone positions. Patients and methods: This is an interventionist study that evaluated eight healthy volunteers. A protocol of HRCT of the lung was performed in three regions: at the apex (2 cm above the aortic level), hilum (1 cm below the carina) and basis (2 cm above the right diaphragm) in the supine position, without and with CPAP of 5, 10 and 15 cmH2O. Also HRCT slices were performed in the prone position at the lung basis, without and with CPAP of 10 cmH2O. All HRCT slices were obtained at the functional residual capacity. Each CPAP level was maintened at least five minutes and the period between the different levels of CPAP was similar. For analysis the results were divided into regions ventral, medial and dorsal and with slices of apex, hilum and basis together. The mean lung densities (MLD) and the percentual of units with densities lower than -950 UH (overinflated) were calculated for each region. Results: There was no difference between the MLD of apex, hilum and basis for the same level pressure. In the supine position, there were a MLD reduction and an increase of the number of pixels on hyperinflated areas according to CPAP levels: without CPAP -761 HU e 7,25%; CPAP 5: -780 HU e 8,57%; CPAP 10: -810 HU e 11,62%; CPAP 15: -828 UH e 14,65% (p< 0,05). The same occurred in the prone position without CPAP: -759 UH e 6,30% and with CPAP 10: -803 UH e 9,94% (p < 0,05). It was observed a crescent ventro-dorsal density gradient in supine position that was inverse in prone position. At CPAP of 10 cmH2O there was lower percentage of pixels on hyperinflated areas in the prone position than in supine. In the non dependent lung regions (ventral in supine and dorsal in prone) there were lower percentage of pixels on hyperinflated areas and higher on normoaerated areas in the prone position than in supine with little differences in the dependent regions. Conclusions: Non invasive CPAP in normal subjects induces progressive overdistension with increase of pressure levels in supine and prone positions. CPAP of 10 cmH2O causes less overdistension of the non dependent regions than the same level of CPAP in supine position, without inducing significant overinflation of the dependent regions. So that the prone position causes a more homogeneous air distribution through the lungs.